The Use of a Structured Form during Urology Out-patient Consultations - Thomas, K.; Emberton, M.; Reeves, B. (Methods of Information in Medicine, 2005)
Objectives: To compare the completeness of documentation in the medical record using a structured form (SF) versus a traditional medical record (TMR).Methods: Randomised controlled trial comparing the use of SF and TMR in urology out-patient clinics for documentation of 15 items of clinical information, time taken to complete and acceptability to clinicians assessed by a self-completion questionnaire. in a teaching and district general hospitalsResults: Four hundred new urology patient consultations, 11 clinicians. Completeness of information was compared between groups based on the medical record alone (SF vs. TMR), medical record plus letter to GP and letter alone. SFs were significantly (p<0.0001) more complete than TMRs for the majority of the items in all three groups. There was no significant difference in the time taken to document information using either type of record. The clinicians generally found the SF acceptable for routine use.Conclusions: Structured forms significantly improved the completeness of documentation for new out-patient consultations in urology.
Keywords: Medical record; structured form; documentation; audit; proforma; out-patient